Elevated temperature and decreased salinity impacts on exogenous Vibrio parahaemolyticus infection of eastern oyster, Crassostrea virginica - Ricketts, Omario M. A.; Isaac, Sean R.; Lara, Rhiannon A.; Mendela, Tyler S.; Enzor, Laura A.; Silver, Adam C. (Frontiers in Microbiology, 2024)
Anthropogenic carbon emissions have resulted in drastic oceanic changes, including increased acidity, increased temperature, and decreased salinity. This project investigated the relationship between projected climate scenarios and their influence on both eastern oyster, Crassostrea virginica, and the aquatic bacteria, Vibrio parahaemolyticus. Few studies have directly assessed the compounded impact of alterations to oceanic conditions on oyster physiology and the relation to the presence of V. parahaemolyticus. Specifically, we examined whether an increase in water temperature and/or decrease in salinity would impair oyster resistance to V. parahaemolyticus, a human food and waterborne pathogen. Using a culturedependent approach, our data revealed that the alterations in environmental conditions did not significantly impact V. parahaemolyticus numbers within oyster hemolymph or tissues. However, we did observe a dramatic increase in the total amount of bacteria and pathogenic native Vibrio species, Vibrio aestuarianus and Vibrio harveyi. Despite detecting V. parahaemolyticus in most tissues at seven days post-challenge, oysters were able to reduce bacterial levels below our limit of detection by 28 days of exposure. Furthermore, in our second experimental trial exploring single vs. multiple inoculation of bacteria, we observed that oysters were either able to reduce total bacterial levels to pre-treatment burdens (i.e., below our limit of detection) or die. Our work demonstrates that the synergistic effects of elevated temperature and decreased salinity do not inhibit oyster from preventing the long-term colonization of exogenous V. parahaemolyticus. However, our data do show these environmental stressors impact oyster physiology and the native microbiota. This can lead to the proliferation of opportunistic pathogens, which could have impacts on oyster population numbers, as well as ecosystem and human health.The eastern oyster, Crassostrea virginica, is an ecologically important keystone species to estuarine environments. Oyster reefs offer a habitat for various aquatic animals, provide protection from coastal erosion, and improve water quality and clarity (Kennedy, 1996). Additionally, oysters are considered a